Non-Alcoholic Beer and Health: A Potential Alternative to Traditional Alcoholic Beer - Skowierzak, Filip; Kozyra, Klaudia; Kozieł-Kwit, Sylwia; Lisik, Bartłomiej; Sado, Aleksandra; Wręczycki, Mariusz; Sawczuk, Kacper; Simlat, Aleksandra; Rogowska, Wiktoria; Szada-Borzyszkowski, Krzysztof (Journal of Education, Health and Sport, 2026)
Background: The consumption of non-alcoholic beer has increased in recent years as it is increasingly perceived as an alternative to traditional alcoholic beverages. This trend reflects growing health awareness and interest in products with potentially more favorable health profiles. Non-alcoholic beer retains certain bioactive compounds found in beer, including polyphenols, vitamins, and minerals, while containing little or no ethanol. Aim: The aim of this study was to review current evidence regarding the effects of non-alcoholic beer on human health and to compare its potential effects with those associated with traditional beer containing ethanol. Material and methods: A narrative literature review was conducted using the PubMed database. The analysis included original studies, clinical trials, observational studies, and review articles examining the effects of non-alcoholic beer on metabolic parameters, liver function, cardiovascular health, gut microbiota, inflammatory processes, and potential neuroprotective effects. Results: Available studies suggest that non-alcoholic beer does not significantly affect metabolic parameters, liver function, or body composition in healthy individuals. Some evidence indicates potential beneficial effects related to lipid profile, gut microbiota diversity, and modulation of inflammatory responses. Conclusions: Non-alcoholic beer may represent a safer alternative to alcoholic beer due to the absence of ethanol while retaining bioactive compounds. However, most studies are short-term and include small populations. Further long-term research is needed to clarify its health effects.